Amicitia and caritas in the 7th Century: Isidore of Seville and His Sources - Vorontsov, Sergey (Ciceroniana On Line, 2017)
Key words: amicitia; caritas; justice; unity; Isidore of Seville; Laelius; Cicero; Visigothic Spain. Abstract: The article studies the reception of Cicero’s Laelius in Isidore of Seville’s sententiae 3, 28-32, that offers the only extant theoretical conceptualization of amicitia as a form of interpersonal relation during the 6th and 7th centuries AD. Over the period, caritas was regularly used to describe social relations. Accordingly, the study’s key question is: how was classical concept of amicitia reintegrated into the Christian discourse of 7th century Roman-Barbarian Spain? The article suggests that the question of true unity in friendship was central for Isidore: he reconsiders patristic model of grounding amicitia in caritas that was interpreted as both the principle of right behaviour towards the neighbour and a ground of general political and religious unity of gens Gothorum. Thus, Isidore attempts to correlate the personal relations of amicitia with the principle of caritas that rules and unites the society. This suggestion helps to explain why Isidore pays attention to the ideal of friendship represented in Cicero’s Laelius. In the final analysis, the study tries to explain why Isidore builds the chapters on friendship from quotations and allusions on Laelius, suggesting that by these means Isidore’s text according to the principles of writing of Late Antiquity, established a set of references between relevant problems of unity and relations in 7th century Visigothic Spain and the authoritative text of the tradition.